Kontroversi Penggunaan Alat Musik dalam Peribadatan Gereja Kristen - Trivena Andrianikus; Herdemei Saerang (LPPM STT Baptis Kalvari, 2023)
The use of musical instruments in Christian church worship has been a subject of debate for many years. While some church denominations permit the use of modern musical instruments, others argue that it goes against church traditions and distracts the congregation from worshiping God. As members of the church, it is important for the congregation to have a thorough understanding of the role of musical instruments in Christian worship, as they have been used in the Bible to glorify God and enhance the worship experience. As the church has evolved, so too has its music, with various new forms of music emerging. The use of music and musical instruments in church services should be clearly defined by church officials, as a complete understanding of church music and musical instruments is essential in expressing Christian worship. The journey of music and musical instruments has become a part of worship services throughout history and their use should always have a clear purpose. Jesus Christ knows the hearts of His people and understands why musical instruments and the voices of worshippers are used in Christian services. This research uses a descriptive qualitative research method. The data collected comes from a literature review and a study of the Bible using text analysis methods to find the Biblical principles.